The Multiple Functions of Common Microbial Carbon Polymers, Glycogen and PHB, during Stress Responses in the Non-Diazotrophic Cyanobacterium Synechocystis sp. PCC 6803 - Damrow, Ramon; Maldener, Iris; Zilliges, Yvonne (Frontiers in Microbiology, 2016)
Classical microbial carbon polymers such as glycogen and polyhydroxybutyrate (PHB) have a crucial impact as both a sink and a reserve under macronutrient stress conditions. Most microbial species exclusively synthesize and degrade either glycogen or PHB. A few bacteria such as the phototrophic model organism Synechocystis sp. PCC 6803 surprisingly produce both physico-chemically different polymers under conditions of high C to N ratios. For the first time, the function and interrelation of both carbon polymers in non-diazotrophic cyanobacteria are analyzed in a comparative physiological study of single- and double-knockout mutants (ΔglgC; ΔphaC; ΔglgC/ΔphaC), respectively. Most of the observed phenotypes are explicitly related to the knockout of glycogen synthesis, highlighting the metabolic, energetic, and structural impact of this process whenever cells switch from an active, photosynthetic ´protein status` to a dormant ´glycogen status`. The carbon flux regulation into glycogen granules is apparently crucial for both phycobilisome degradation and thylakoid layer disassembly in the presence of light. In contrast, PHB synthesis is definitely not involved in this primary acclimation response. Moreover, the very weak interrelations between the two carbon-polymer syntheses indicate that the regulation and role of PHB synthesis in Synechocystis sp. PCC 6803 is different from glycogen synthesis.